PENGARUH LINGKUNGAN DAN PELATIHAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT. NYONYA MENEER SEMARANG - Asri Puspasari; Handoyo Djoko Waluyo; Agung Budiatmo (Universitas Diponegoro, 2013)
The purpose of this study was to determine the effect of training and working environment of the employees' performance of PT. Nyonya Meneer Semarang. Type of research is explanatory research with sample size about 85 employees at the staff. The data were analyzed quantitatively by Simple Linear Regression, Multiple Linear Regression, Z test and F test were performed with SPSS version 11.0, and also performed a qualitative analysis. Training which include: communication training, customer service training, salesmanship training, training in the discussion of consumer protection laws and training on the implementation of policy. Results and discussion of the studies suggest that there is a significant relationship between training and job performance that is equal to 37.4%, which means the training factor determining employee performance by 37.4%. Z test of significance test is known that the value of z 4.715 count is greater than z table is 1.96, which means there is a positive effect between training and job performance, which means any improvements to the training will affect job performance in the same direction. While the work environment include: air temperature, noise, cleanliness, scientific equipment, lighting horizontal and vertical relationships between superiors and subordinates, aspires freedom and responsibility appropriate authority. From the results and discussion stated that there is a significant relationship between work environment with job performance that is equal to 45.3%, which means the work environment factors determining employee performance by 45.3%. While the z test of significance test is known that the value of z 4.064 count is greater than z table is 1.96, which means there is a positive influence between work environment and job performance, which means that changes in working towards environmental improvements that will positively affect work performance in the same direction. training variables and the work environment positive effect on employees 'performance by 53.5%, which means that 53.5% of employees' performance is determined by training and work environment factors.